Hybrid Artificial Intelligent Systems: 16th International Conference, HAIS 2021, Bilbao, Spain, September 22-24, 2021, Proceedings - Sanjurjo González, Hugo; Pastor López, Iker; García Bringas, Pablo; Quintián, Héctor; Corchado, Emilio (Lecture Notes in Computer Science, 2021)
This book constitutes the refereed proceedings of the 16th International Conference on Hybrid Artificial Intelligent Systems, HAIS 2021, held in Bilbao, Spain, in September 2021.The 44 full and 11 short papers presented in this book were carefully reviewed and selected from 81 submissions.